47.9k views
1 vote
C₇H₉+ HNO₃ → C₇H₆(NO₂)₃+ H₂O Balance the formula

1 Answer

4 votes

Hey there!

C₇H₉+ HNO₃ → C₇H₆(NO₂)₃+ H₂O

Our elements: C, H, N, and O.

Balance H.

Ten on the left, eight on the right. Add a coefficient of 2 in front of H₂O.

C₇H₉+ HNO₃ → C₇H₆(NO₂)₃+ 2H₂O

Balance N.

One on the left, three on the right. Add a coefficient of 3 in front of HNO₃.

C₇H₉+ 3HNO₃ → C₇H₆(NO₂)₃+ 2H₂O

This unbalanced H, let's increase the coefficient in front of H₂O from 2 to 3 to rebalance.

C₇H₉+ 3HNO₃ → C₇H₆(NO₂)₃+ 3H₂O

Balance O.

Nine on the left, nine on the right. Already balanced.

Balance C.

Seven on the left, seven on the right. Already balanced.

Our final balanced equation:

C₇H₉+ 3HNO₃ → C₇H₆(NO₂)₃+ 3H₂O

Hope this helps!

User Heny
by
4.8k points